Development and Design of 35KW Low-Noise IPM Motor for Micro Electric Vehicles - 박형삼; 안덕근; 김동철; 이상현 (International Journal of Advanced Culture Technology(IJACT), 2023)
Since the electric vehicle uses an electric motor, problems have arisen as the driver hears the inherent noise of the motor or external noise, which was not a problem in the past, due to the overall lower noise environment than when using an internal combustion engine. Therefore, the purpose of this paper is to reduce the noise and vibration of electric motors for electric vehicles, and recently, to increase the speed of high-power, high-efficiency electric motors in a small size, and to develop low-noise motors, IPM motors are applied to produce 35KW electric motors for electric vehicles. A motor for low noise was designed and implemented. N-T Curve and efficiency map were confirmed as the final result of developing a 35KW low-noise motor for electric vehicles by applying the IPM motor applied in this paper. Based on 3500 rpm, Max Torque [Nm]: 121.15, Max Power [KW]: 44.04, and Max Efficiency [%]: 97.65, showing high efficiency.